Strategic environmental risk management in South African companies - Kitsikopoulos, Claudia (My University, 2018)
ABSTRACT Past and current corporate sustainability management approaches to natural resource use have been characterised by a short-term financial focus, while natural systems have been viewed as stable, linear and predictable. This approach disregards the multidimensional characteristics of social-ecological systems, of which humanity forms an integral part. Such systems are dynamic, complex and non-linear in space and time and can change in unpredictable ways. Human activities have led to a significant increase in the pressure on ecosystem services, resulting in severe degradation of most ecosystems and causing the global ecological system to become increasingly unstable and unpredictable and weakening the planet’s ecological resilience. To account for these dynamics, the sustainability concept has evolved from conceptualising the Triple Bottom Line (TBL) model, still giving preference to the financial aspects of business conduct, to applying risk and resilience theory. To manage natural resources more sustainably, reduce risk exposure resulting from natural resource degradation and ensure sustained human wellbeing, more strategic approaches are required by integrating environmental risks into corporate sustainability management practices to establish whether these are aligned with risk and resilience thinking as part of sustainable development. It will also identify whether businesses are starting to reconsider their position as part of a complex social-ecological system, and not as separate entities disconnected from it. A reassessment of corporate sustainability practices is necessary to enable sustainable management of natural resource use and enhance resilience during times of increasing uncertainty and unpredictability. The aim of my PhD thesis was to advance our understanding of whether businesses address social-ecological system complexity as part of their business strategy and the risks associated with ecosystem degradation to strengthen resilience. Annual, integrated and sustainability reports of 30 of the Top 100 Johannesburg Stock Exchange (JSE)-listed companies were assessed on the quality of environmental iv impact disclosures between 2008 and 2013 as well as on the extent of environmental risk reporting between 2008 and 2015. To identify whether company reports address system complexity indicating a paradigm shift in business practices, annual, integrated and sustainability reports were compared to two risk maps that were created from existing literature. Interviews with sustainability managers were conducted to identify factors affecting environmental reporting and management as well as strategic environmental risk management approaches. The environmental impact disclosure quality was found to be average to poor and environmental risks were rarely addressed. The most frequently reported environmental risk was related to water and climate change with 20-25% in 239 reports. These were connected to other sustainability and business risks or strategic objectives in only few cases. Interviews suggest that JSE listing requirements, King III and other legal obligations appeared to be a driving force in moving businesses towards sustainable practices but that reporting fatigue, as well as resource and time constraints were found to negatively affect the advancement of corporate sustainability. Further, understanding of complexity and acknowledgement of business’ dependence on natural capital and strategic management of environmental risks were rarely evident. The findings indicate that, while the sustainable development concept has shifted towards multi-level, multi-system complexity of social-ecological systems of which businesses are a part, corporate sustainability still displays a disconnection from the system as well as short-term, linear and retrospective views and management approaches. The ability to sustain economic, social and environmental wellbeing during and after the planet’s transition from a stable state to a new, unpredictable one is thus compromised. Some companies were found to practice strategic environmental risk management, thus creating a resilient business and providing long-term value to all parties involved and affected by their business operations. A number of recommendations are made that could advance corporate sustainability.
Keywords: Industrial management--Environmental aspects; Corporate governance; Disclosure in accounting